Utilization And Characterizaation Of CaO Nanocatalyst From Duck Eggshell Impregnated With NaOH And Its Application In Biodiesel Production From Cooking Oil - dede Arief Mahendra (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2025)
Global energy demand, including in Indonesia, remains heavily dependent on non-renewable sources (fossil fuels), whose reserves are steadily depleting. The combustion of these fuels releases various pollutants into the atmosphere, including carbon dioxide (CO₂), sulfur dioxide (SO₂), and nitrogen oxides (NOx), which contribute to air pollution, acid rain, climate change, and adverse human health effects such as respiratory and cardiovascular diseases. This condition underscores the urgent need for the development of environmentally friendly alternative fuels such as biodiesel. This study aims to synthesize biodiesel from waste cooking oil through a transesterification reaction using a catalyst derived from duck eggshells, which was converted into a NaOH-impregnated CaO nanocatalyst. The nanocatalyst was prepared via the sol-gel method with continuous stirring for 3 hours at 4000 rpm. NaOH impregnation was applied at concentrations of 35%, 45%, and 55% of the total catalyst weight. The resulting sol-gel was separated from the residue, dried, and then calcined at 900°C for 1 hour, producing nanocatalysts designated as 35NaOH/CaO, 45NaOH/CaO, and 55NaOH/CaO. The catalysts were characterized using FTIR, XRD, and PSA. The transesterification reaction was carried out at 60°C for 2 hours, with an oil-to-methanol molar ratio of 1:9 and a catalyst loading of 3% by weight relative to the oil. The biodiesel produced was characterized using GC-MS, yielding the highest methyl ester content of 99.89% with the 55NaOH/CaO catalyst. These results indicate that the biodiesel produced had a high level of purity and complied with the EN 14103 standard.